Development of Mathematics Teaching Materials on Tri-N-Based Variable Linear Equations and Inequalities - Akhmad Nayazik; Handini Arga Damar Rani (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2023)
Teaching materials are learning tools that contain materials, learning methods, and ways of evaluating students which are arranged systematically to achieve learning objectives. The teaching materials used during mathematics learning are textbooks which make it difficult for students to understand the material and educators have not developed teaching materials using Tri N teachings. This study aims to determine the validity and response of students to the development of mathematics teaching materials using Tri N teachings on material One Variable Linear Equations and Inequalities. This type of research is Research and Development (R&D) which aims to produce and test product quality. This research refers to the 4D development model, namely Define, Design, Develop, and Disseminate. However, this research only reached the develop stage. Data collection was carried out using documentation techniques, validation sheets and student response questionnaires. The test subjects were class VII students of MTs Al Hidayah Sadeng. The data analysis technique used is descriptive analysis. This research produced mathematics teaching material products with an average percentage of 85.6% which were included in the very valid category. Student responses to teaching materials are in the very good category with an average percentage of 82.22%. This shows that teaching materials are appropriate for use in learning at school.